Non-nutritive sucking milestones of preterm infants in Indonesia: a descriptive study - Luh Karunia Wahyuni; Irawan Mangunatmadja; Risma Kerina Kaban; Elvie Zulka Kautzia Rachmawati; Melinda Harini; Budiati Laksmitasari; Agatha Geraldyne; Inez Ayuwibowo Sangwidjojo; Dini Prima Utami; Victor Prasetyo Poernomo; Adrian Prasetya Sudjono (Paediatrica Indonesiana, 2022)
Background Non-nutritive sucking (NNS) maturity has been used as one of the markers of oral feeding readiness in infants. Prematurity may hinder the attainment of NNS milestones. Depending on gestational age (GA) at birth, preterm infants may display various degrees of immaturity, potentially affecting the strength, coordination, and efficiency of skills required for NNS. Objective To identify the progression of NNS patterns across gestational age groups of preterm infants in Indonesia by comparing NNS parameters between moderate-to-late preterm and very preterm infants. Methods NNS evaluation was conducted in 120 preterm infants born at 28-34 weeks gestational age in five tertiary hospitals in Jakarta, Indonesia. Three aspects of NNS (suction pressure, number of suctions per burst, and time between bursts) were documented and arranged to present a descriptive overview. A suction pressure measurement device was used to record, identify, and analyze NNS parameters. We hypothesize that maturity, as determined by GA, positively affected the attainment of NNS milestones. Results Moderate-to-late preterm infants (GA 32 to <37 weeks), compared to very preterm infants (GA 28 to <32 weeks), had higher mean NNS pressure (-79.8 vs. -72.7 mmHg, respectively, P=0.041) and shorter mean time between bursts (6.63 vs. 7.36 s, respectively, P=0.030). Mean number of suctions per burst were also significantly different between the two GA groups (8.90 vs. 8.99 sucks/burst, respectively, P=0.048). Conclusion Maturity, as reflected by GA, had a positive effect on the attainment of NNS milestones in preterm infants in Indonesia. Significant differences in the three NNS parameters: number of suctions per burst, time between bursts, and suction pressure were found between moderate-to-late preterm and very preterm infants.